Impact of COVID-19 lockdown on people living with diabetes: Experience from a low-middle income country in South Asia - Dissanayake, Harsha; Soysa, Pasindu; Samarathunga, Thilina; De Silva, Laksara; Samaranayake, Nadeesh; Padmaperuma, Chanya; Katulanda, Prasad (Elsevier, 2022)
AIMS: COVID-19 lockdown imposes many challenges to patients with diabetes. We aimed to assess the impact of COVID-19 lockdown on health-related behavior and disease control among patients with diabetes. MATERIALS AND METHODS: A cross-sectional study was conducted among adults with diabetes attending a diabetes clinic in Colombo, Sri Lanka in June-July 2020. Lifestyle and disease control changes before and during the lockdown, were determined using an interviewer-administered questionnaire and review of medical records. RESULTS: Among 1727 participants mean HbA1c decreased by 0.30% (95% CI 0.24-0.36, p < 0.001). HbA1c improved in 37.6% but deteriorated in 18.8%. Male sex (OR 1.36, 95% CI 1.10-1.67), better education (OR 1.10, 95% CI 1.01-1.20) and being employed (OR 1.08, 95% CI 1.00-1.16) were sociodemographic predictors of improved control. Better dietary adherence (OR 1.55, 95% CI 1.13-2.12), night-time sleep (OR 1.46, 95% CI 1.13-1.88) and indoor exercise (OR 1.62, 95% CI 1.23-2.07) were behavioural determinants of improved glycaemia. Decreases in self-monitoring of blood glucose (OR 1.45, 95% CI 1.09-1.93), exercise (OR 1.7, 95% CI 1.32-2.20), medication use (OR 1.95, 95% CI 1.37-2.78), dietary adherence (OR 1.72, 95% CI 1.32-2.26) and family income (OR 1.45, 95% CI 1.12-1.88) predicted worsening glycaemia. Only 4.1% used telehealth services; 83.1% of them reported good satisfaction. CONCLUSIONS: Mean HbA1c improved during the lockdown. Overall, 37.6% of participants improved their glycaemic control. Well-educated employed men were more likely to improve glycaemic status. Improving diabetes control through healthy lifestyle practices and self-monitoring are feasible even in resource limited settings.
Keywords: COVID-19; Diabetes; Lifestyle; Self-monitoring of blood glucose; South Asia